Productivity Signalling and Further Training : evidence on Absence Behaviour, Presentecism and Overtime Hourts of Geman Employees - Brändle, Tobias [Verfasser] (My University, 2015)
"This paper pursues the argument that there is an incentive for employees to signal productivity in order to get further training in a firm. While usually both sides can benefit from this, firms are harmed if employees invest too much effort in potentially inefficient effort signals. Using representative survey data the paper empirically analyses whether different productivity signals increase the chances of further training for German employees. On the one hand, the results show that individuals who come to work when they are ill and who put up overtime hours can have higher chances to receive further training. On the other hand, it is found that individuals who report in sick are also more likely to receive further training. The observed relation suggests that only a moderate use of these effort signals is exerted. Therefore, negative consequences for firms due to effort spent in potentially inefficient effort signals might be modest." (author's abstract, BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Betriebliche Weiterbildung; Weiterbildungsbeteiligung; Einflussfaktor; Arbeitsproduktivität; Arbeitsmotivation; Leistungsmotivation; Arbeitnehmer